PENERAPAN MEDIA QUIZIZZ PADA PEMBELAJARAN BAHASA INDONESIA TERHADAP HASIL BELAJAR SISWA KELAS IV DI SDN 82 SINGKAWANG - Dwi Febrianti Nadila; Dina Anika Marhayani; Dewi Mariana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: (1) determine the differences in learning outcomes for class IV students after applying Quizzizz media to Indonesian language learning; (2) knowing students' responses to quizizz media in learning Indonesian for class IV students. This research is a quantitative experimental research. This research method is a True Experiment. The population of this study was all class IV students, totaling 50 students. Samples were taken using total sampling technique. Data collection techniques use test and non-test techniques. The data analysis technique used was the two-sample t test and the percentage of student responses. The results of the research show that: (1) there are differences in learning outcomes for class IV students after applying Quizzizz learning media to Indonesian language learning with tcount = 6.383 > ttable = 2.010; (2) Positive student response to quizizz media in learning Indonesian for class IV students with a percentage of 84% in the very high category. Thus, it can be concluded that there is an influence on quizizz media on Indonesian language learning for class IV students.